COMPARATIVE STUDY OF ISLAMIC CREDIT CARDS TO BE ACCEPTED: MUSLIM CONSUMERS’ PERCEPTIONS - Chowdhury, Md. Shahnur Azad; Shahabuddin, A M; Ullah, Habib; Haque, Md. Shariful; Ahmmed, Monir (American International Journal of Social Science Research, 2023)
The use of standard credit cards, which incorporate the practice of riba in the case that a late payment is made, has resulted in a conflict with the perspectives of Muslim clients, which is to be addressed in choosing the best alternative available cards.   The primary purpose of this research is to analyze the many existing models of Islamic credit cards to determine which one is most in line with Sharia law. The kind of study that has been done is descriptive, which employed rigorous literature studies and investigated the existing theories. The holy Quran is the source of the fundamental laws that govern what is and is not allowed in terms of credit and debt. After then, the attributes of the cards that are being presented are analyzed in light of those principles to ensure that they adhere to Sharia, which is a religious law. The Muslim community has access to a wide range of credit card options to pick from. Charge cards, Qard Al-Hasan cards, Bai Al-Inah cards, Mushraka Mutanqisa cards, Tawarruq cards, and Murabahah cards are all included in the bundles. Also had are Tawarruq cards and Murabahah cards. Critiques raised voices against Islamic credit cards. Consequently, there is a need for a payment method that may function like a credit card. However, they are still obligated to maintain complete conformity with Islamic principles. This article takes a closer look at the packages mentioned above to understand better the degree to which the various options are accepted. The study explored the crucial features of the existing Islamic credit cards and evaluated the shariah compliance of those concepts. According to the findings and conclusions of the study, the authors concluded that the 'Mushraka Mutanqisa' is the most Shara-compliant and hence most likely to be approved by Muslim customers.JEL Classification Codes: G21.